HUBUNGAN GAYA BELAJAR TERHADAP INDEKS PRESTASI KUMULATIF (IPK) MAHASISWA PSKPS FKIK ULM - Dawenan, Febrina Rannu; Nurikhwan, Pandji Winata; Husin, Gt. Muhammad Irhamna (Universitas Lambung Mangkurat, 2024)
Abstract: Learning style has an important role in the learning process. Student learning achievement can be seen in the Grade Point Average (GPA). The main objective of this study is to determine whether there is a relationship between learning style and GPA. This study used an analytic observational method with a cross-sectional research design. To determine student learning styles carried out by filling The VARK Questionnaire. The results are divided into 2 categories. Categorized as unimodal if one of the four learning styles is dominant, either visual, auditory, reading/writing, or kinesthetic and categorized as multimodal if having more than one learning styles. Student GPA data was obtained from the medical education unit of PSKPS FKIK ULM. The number of samples in this study was 215. The distribution of this research sample is unimodal learning style (49.3%) and multimodal learning style (50.7%) then for student GPA for < 2.75 (18.1%) and ≥ 2.75 (81.9%). Based on the chi-square test, obtained p = 0.011. It can be concluded that there is a significant relationship between learning styles and student GPA. Keywords: learning style, VARK, Grade Point Average, learning achievement, the VARK questionnaire. Abstrak : Gaya belajar mempunyai peranan yang penting dalam proses pembelajaran. Prestasi belajar mahasiswa dilihat dalam Indeks Prestasi Kumulatif (IPK). Tujuan penelitian ini untuk mengetahui apakah terdapat hubungan antara gaya belajar dengan IPK. Menggunakan metode observasional analitik dengan desain penelitian potong lintang (cross-sectional). Penentuan gaya belajar mahasiswa dilakukan dengan mengisi The VARK Questionnaire. Hasil pengisian terbagi menjadi 2 kategori. Dikategorikan sebagai gaya belajar unimodal jika salah satu dari keempat gaya belajar yang dominan yaitu visual, auditori, reading/writing, atau kinestetik dan multimodal jika memiliki lebih dari satu gaya belajar. Data IPK mahasiswa didapatkan dari medical education unit PSKPS FKIK ULM. Jumlah sampel penelitian ini adalah 215. Sebaran sampel penelitian ini adalah gaya belajar unimodal (49,3%) dan gaya belajar multimodal (50,7%) kemudian untuk IPK mahasiswa adalah IPK < 2,75 (18,1%) dan IPK ≥ 2,75 (81,9%). Berdasarkan uji chi-square, didapatkan p = 0,011. Kesimpulannya adalah terdapat hubungan yang signifikan antara gaya belajar dengan IPK mahasiswa. Kata-kata kunci: gaya belajar, VARK, Indeks Prestasi Kumulatif, prestasi belajar, kuesioner gaya belajar VARK.